Pendekatan Ergonomi menggunakan NBM dan REBA untuk Merancang Fasilitas Kerja Pengupasan Kelapa Parut: Studi Kasus di Sebuah Toko Sayuran - Sundari, Anggina Sandy; Sari, Annisa Rizkiana; Rimantho, Dino; Ningtyas, Desinta Rahayu (Engineering Faculty at Universitas Singaperbangsa Karawang, 2023)
Mannisa's Vegetable Store is a business that provides grated coconut. Before being grated, the coconut has to be peeled where the activity is still carried out conventionally. Based on initial observations, the two workers experienced complaints. The purpose of this study is to identify the body parts with the highest complaints and to analyze work postures so that ergonomic work facilities can be designed. The method for identifying complaints is NBM, while the method for analyzing work posture is REBA. The determination of design size uses anthropometric data from Indonesians. Based on NBM, the highest complaint felt has a value of 3 or the equivalent of 75% where this value stated that the complaint felt was in the category pain. Based on REBA, the risk value for stripping activity of coconut shells and husks was 8 to 10 or high risk. The work facility designed as an improvement is a work table with a standing job position.